Designing a stakeholder-informed digital learning model integrating virtual reality and e-learning for complementary therapy-based postpartum preeclampsia education - Rini, Susilo; Sandi, Arif Setia; Ma’rifah, Atun Raudotul; Maya, Raden Ayu Aminah (Universitas Muhammadiyah Purwokerto, 2026)
Background: Postpartum preeclampsia remains a significant contributor to maternal morbidity and mortality in Indonesia. Midwives, as frontline maternal health providers, are expected to deliver holistic care; however, structured learning models integrating complementary therapies within digital education platforms remain limited. Although virtual reality (VR) and e-learning have been widely applied in healthcare education, their context-sensitive integration into postpartum preeclampsia management training has not been sufficiently explored. Objective: This study aimed to explore stakeholder perspectives and to design a stakeholder-informed conceptual digital learning model integrating complementary therapies into VR- and e-learning-based midwifery education. Methods: This qualitative exploratory study involved 31 participants, including practicing midwives, educational practitioners, policymakers, and clinical and technology experts in Banyumas Regency, Indonesia. Data were collected through focus group discussions and semi-structured in-depth interviews and analyzed using thematic analysis to identify stakeholder perspectives, contextual challenges, and design requirements informing the development of a conceptual digital learning model. Results: Four interconnected themes were identified: 1) fragmented integration of complementary care; 2) the need for experiential and clinically contextualized learning; 3) digital readiness and structural constraints; and 4) the importance of institutional support and policy alignment. These findings informed the development of a stakeholder-informed conceptual framework consisting of structured curriculum modules, a nine-scene VR storyboard simulating clinical decision-making, and a mobile-accessible Learning Management System integrating complementary therapies such as lavender aromatherapy, warm foot bath, and slow-stroke back massage. Conclusion: This study provides a contextually grounded digital learning framework for integrating VR, e-learning, and complementary therapies in postpartum preeclampsia education. The proposed model offers a foundation for future pilot implementation and effectiveness studies to evaluate its impact on midwifery competencies and clinical practice.